2021
DOI: 10.21832/kiaer1609
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Foreign Language Anxiety

Abstract: This book presents original research on the effects of foreign language anxiety (FLA) on young language learners. It includes suggestions for alleviating FLA and encouraging foreign language enjoyment which will ultimately facilitate more effective language learning and support children’s psychosocial wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In most contexts, early FL learning, overwhelmingly English, was offered following parental interest and pressure (e.g., in 16 European countries and Australia, Hong Kong, Canada, and USA: Nikolov & Curtain, 2000;in Portugal: Mourão, 2019). This trend energized "English fever" (in Indonesia: Kiaer et al, 2021) and "Englishization" (in the Netherlands: Keydeniers et al, 2021). In South America, and on other continents, early English learning is seen as a means of "opening doors" (Sayer, 2018).…”
Section: Language Policy Documents On Preschool Fl Teaching and Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…In most contexts, early FL learning, overwhelmingly English, was offered following parental interest and pressure (e.g., in 16 European countries and Australia, Hong Kong, Canada, and USA: Nikolov & Curtain, 2000;in Portugal: Mourão, 2019). This trend energized "English fever" (in Indonesia: Kiaer et al, 2021) and "Englishization" (in the Netherlands: Keydeniers et al, 2021). In South America, and on other continents, early English learning is seen as a means of "opening doors" (Sayer, 2018).…”
Section: Language Policy Documents On Preschool Fl Teaching and Learningmentioning
confidence: 99%
“…The dynamics play out in specific contexts in different ways. In South Korea, for example, Kiaer et al (2021) found positive relationships between how much English was used in two types of kindergarten programs and the children's level of anxiety. Parents with higher ambitions placed their children in more intensive (immersion-like) programs.…”
Section: Public Attitudes Towards An Early Start Of Fl Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet parents', teachers', and others' expectations in exam-oriented contexts, many English as a Foreign Language (EFL) students study English to pass exams but rarely speak it (Kim, 2021). As many of these EFL students do not speak English well, they often do not enjoy learning the language, lack confidence, and may feel anxious or reluctant to speak English (Kiaer et al, 2021). For example, Swedish students in multilingual, communicative-oriented contexts were more willing to communicate in a second language (L2 WTC) than Korean students in monolingual, exam-oriented contexts (Lee & Sylvén, 2021).…”
mentioning
confidence: 99%